PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI ANDROID UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA KOMPETENSI DASAR SISTEM TRANSMISI MANUAL - Jatsiah, Anisa Nur; Roziqin, Ahmad (Automotive Science and Education Journal, 2021)
Abstract The purpose of this research is to develop interactive learning media based on android applications on the basic competencies of applying the way of maintenance and periodic maintenance of manual transmission systems, testing media feasibility, testing differences in learning outcomes, and knowing the responses of learners to the media that has been developed. This research uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Testing using Pre Experimental Design (nondesign) model with one group pretest-postest design experiment model. Based on the results of the study showed the feasibility results by media experts and material experts get a score with a percentage of 80.6% and 95.3 % fall into the category of "Very feasible". For the improvement of learning outcomes can be seen from the value produced through pretest and posttest produced an average value of 60.2 and 83.6, t-test obtained thitung= value = 13.37 and ttable = 2.04 showed a significant difference, the result of test N-Gain of 0.58 falls into the category of increase "medium". Analysis of student responses obtained amounted to 86,8% are excellen. Keywords: ADDIE, Android, Manual Transmission Systems